Determination of Aquatic Weed for Shelter in Rearing Juvenile Snakehead Channa striata in Pond - Adang Saputra; Reza Samsudin (JURNAL PERIKANAN DAN KELAUTAN, 2017)
A seed of Snakehead Channa striata has characterization an aggressive and or moving as well. One effort to suppress the aggressive nature is through the use of shelter (shelter) of aquatic weeds water hyacinth in maintenance ponds. Therefore, an experiment in aim of evaluation wide water hyacinth for shelter pond to increase growth and survival of Snakehead Channa striata juvenile was conducted. The treatment were various aquatic weeds are: water cabbage Pistia stratiotes, Azolla Azolla piñata, and water hyacinth Eichornoa crassipes. Snakehead juvenile of 5 ± 0.02 cm in total body length and 4 ± 0.01 g in weight were stocked in 9 experimental ponds at 100 juvenile / m3 (350 juvenile / pond). Artificial diet of 33% protein was fed on the juvenile at a rate 5% of biomass a day. Rearing period was conducted for four months. The experimental results showed shelter very important for rearing juvenile Snakehead. The best shelter of aquatic weed in snakehead pond culture was at water hyacinth with survival rate 78.00±2.11% and feed efficiency of 30.8 ± 1.22%. This result could be reffered in snakehead nursery in pond.